Alleviating effect of Lactobacillus fermentum E15 on hyperlipidemia and hepatic lipid metabolism in zebrafish fed by a high-fat diet through the production of short-chain fatty acids - Chen, Yishu; Zheng, Kangdi; Leng, Yang; Zhang, Zhao; Li, Xiaoling; Li, Xiaoyan; Ou, Huajun; Wen, Muhao; Qiu, Feng; Yu, Huajun (Frontiers in Nutrition, 2025)
IntroductionHyperlipidemia is regarded as one of the crucial factors leading to atherosclerosis and other cardiovascular diseases. Gut microbiota plays an important role in regulating host lipid metabolism. Nevertheless, the exact mechanisms behind this remain unclear.MethodsIn the present study, a hyperlipidemic zebrafish model was established using a high-cholesterol diet (HCD) to evaluate the anti-hyperlipidemic effects of Lactobacillus fermentum E15 (L. fermentum E15).ResultsResults showed that L. fermentum E15 effectively reduced lipid accumulation in the blood vessels and liver of HCD-fed zebrafish larvae. Meanwhile, L. fermentum E15 improved abnormal lipid levels, and normalized liver enzyme activity. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis revealed that L. fermentum E15 downregulated the expression of sterol regulatory element-binding factor (SREBP-1), peroxisome proliferator-activated receptor-gamma (PPAR-γ), and fatty acid synthase (Fasn), while upregulated peroxisome proliferator-activated receptor-alpha (PPAR-α). Additionally, metabolomic analysis revealed that L. fermentum E15 produced a series of short-chain fatty acids (SCFAs), including acetic acid, propionic acid, butyric acid, and isovaleric acid. Notably, isovaleric acid contributed to the reduction of lipid droplet accumulation in the liver and blood vessels of HCD-fed zebrafish larvae. In contrast, blocking G-protein coupled receptor 43 (GPR43) with pertussis toxin (PTX) abolished the effects of L. fermentum E15 and isovaleric acid on reducing lipid accumulation in HCD-fed zebrafish larvae. RT-qPCR results further suggested that both L. fermentum E15 and isovaleric acid promoted the expression of GPR43 and leptin A, which was inhibited by PTX.ConclusionThese findings suggested that L. fermentum E15 alleviates HCD-induced hyperlipidemia by activating GPR43 through SCFAs.